2000
DOI: 10.2169/internalmedicine.39.646
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Fabry's Disease Presenting with Cholesterol Crystal Embolization.

Abstract: Wedescribe a 65-year-old manwho presented with pulmonary hemorrhage and progressive renal insufficiency three monthsafter resection surgery for an abdominalaortic aneurysm. Intensive treatment with corticosteroids and hemodialysis were not effective, and the patient died. Postmortemexamination of the kidneys revealed widespread cholesterol clefts within the renal arterioles and a number of lamellar inclusion bodies were observed by electron microscopy. The diagnosis of Fabry's disease was made by the absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Hypercholesterolaemia with a markedly raised HDL-cholesterol was observed in patients with Fabry disease [7] and was previously associated with the occurrence of cardiovascular disease [8]. Atherosclerosis was previously described in several case studies [9], [10], [11].…”
Section: Introductionmentioning
confidence: 92%
“…Hypercholesterolaemia with a markedly raised HDL-cholesterol was observed in patients with Fabry disease [7] and was previously associated with the occurrence of cardiovascular disease [8]. Atherosclerosis was previously described in several case studies [9], [10], [11].…”
Section: Introductionmentioning
confidence: 92%
“…The only endothelial cell populations free of, or with limited storage, are in the liver [7] and adrenal cortical sinusoids and epithelium. In the heart, storage of glycolipid occurs in perinuclear lysosomes within cardiocytes [8] and in the conduction system [9], but signs of atherosclerosis have only occasionally been described [10]. Elleder et al found that within the arterial wall, storage was predominantly in the endothelium and smooth muscle cells of the media, leading to a thickened extracellular matrix layer resembling basement membrane material.…”
Section: Abstract: Fabry Disease Therapy Vasculopathymentioning
confidence: 99%
“…The only endothelial cell populations free of, or with limited storage, are in the liver 7 and adrenal cortical sinusoids and epithelium. In the heart, storage of glycolipid occurs in perinuclear lysosomes within cardiocytes 8 and in the conduction system 9, but signs of atherosclerosis have only occasionally been described 10. Elleder et al found that within the arterial wall, storage was predominantly in the endothelium and smooth muscle cells of the media, leading to a thickened extracellular matrix layer resembling basement membrane material.…”
Section: Vascular Pathology In Fabry Diseasementioning
confidence: 99%